Overviews of reviews on patient compliance with medication protocols used in highly active antiretroviral therapy - Liang Fu; Yan Hu; Hong-Zhou Lu (Elsevier, 2015)
Purpose: To provide evidence support for the development of clinical practice guidelines regarding patient adherence to medication protocols used in highly active antiretroviral therapy (HAART) in China. Methods: We analyzed information contained in recent systematic reviews and meta-analyses regarding patient compliance with medication protocols used in HAART. Results: Nine systematic reviews and one meta-analysis were included in our study which involved three different aspects of patient compliance: influencing factors, assessment methods, and interventions. Conclusions: The high quality data obtained from our study was suitable for use in developing clinically useful guidelines for patent compliance with HAART medication protocols.